1998
DOI: 10.1152/ajpheart.1998.275.3.h1016
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines depress cardiac efficiency by a nitric oxide-dependent mechanism

Abstract: Proinflammatory cytokines (interleukin-1β, tumor necrosis factor-α, and interferon-γ; Cytomix) depress myocardial contractile work partially by stimulating expression of inducible nitric oxide (NO) synthase (iNOS). Because NO and peroxynitrite inhibit myocardial O2 consumption (MV˙o 2), we examined whether this mechanism contributes to reduced cardiac work. In control isolated working rat hearts, cardiac work was stable for 60 min, followed by a decline from 60 to 120 min, without change in MV˙o 2. Cardiac eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 47 publications
3
47
0
2
Order By: Relevance
“…Previous studies have demonstrated that TNF-␣ can directly decrease calcium release within the myocytes, possibly mediated by sphingomyelin pathways. 22,23 Indirect myocardial depression via upregulation of the inducible form of nitric oxide synthase 24,25 can in turn induce desensitization of myofilaments to intracellular calcium, 26 as well as modulate the contractile response to adrenergic stimulation. 27 These may be initially protective mechanisms attempting to decrease the amount of mechanical work output by the heart during acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TNF-␣ can directly decrease calcium release within the myocytes, possibly mediated by sphingomyelin pathways. 22,23 Indirect myocardial depression via upregulation of the inducible form of nitric oxide synthase 24,25 can in turn induce desensitization of myofilaments to intracellular calcium, 26 as well as modulate the contractile response to adrenergic stimulation. 27 These may be initially protective mechanisms attempting to decrease the amount of mechanical work output by the heart during acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…33 After MI, TNF-is induced by invading inflammatory cells and the infarcted and non-infarcted cardiac myocytes produce a high level of NO and NO products, such as peroxynitrite, especially in the infarcted and border zone areas. 34,35 The concentrations of NO and TNF-in patients with congestive heart failure increase in proportion to the severity of heart failure, indicating a role of TNF-in enhanced systemic and local production of NO. 36 Our study is the first to demonstrate weaker expression of 3-nitrotyrosine in infarcted myocardium in KO mice than in WT mice, and this attenuation of 3-nitrotyrosine expression in the KO mice is at least partly attributed to less inflammatory cells invading after MI.…”
Section: Tnf-and Nomentioning
confidence: 99%
“…Additionally, BNP exerts a cardiac antihypertrophic action independent of the endothelial NO production in diabetic rats (32). In septic shock, Gram-negative organisms mediate myocardial depression by a mechanism that involves NO release (33). By a similar mechanism, S aureus alpha toxin produces coronary vasoconstriction and myocardial depression (34).…”
Section: Discussionmentioning
confidence: 99%